Role of AI in Russia Ukraine War and Its Impacts on Europe - Hira Riaz (Social Science Review Archives, 2025)
This study examines the transformative impact of Artificial Intelligence (AI) on modern warfare, particularly in the Russia-Ukraine conflict, and its implications for European security. Using a neorealist framework, the research analyzes how AI is reshaping the balance of power in Europe, creating new security challenges, and influencing the geopolitical landscape. The findings highlight the need for a unified European approach to regulating military AI, addressing ethical concerns, and promoting cooperation to mitigate the risks and harness the benefits of AI in defense.